Unmet needs of people with epilepsy: A qualitative study exploring their journey from presentation to long-term management across five European countries - Graham-Rowe, Ella; Katzer, Caroline Brigitte; Riaz, Sumira; Attwood, Amanda; Bates, Liz; Sainz-Fuertes, Ricardo; Swan, Becky (Frontiers in Neurology, 2023)
Epilepsy is a neurological disease that can negatively impact a person’s physical, psychological, social, and emotional well-being. The aim of this study was to provide insights into the experiences of people with epilepsy on concomitant therapy, i.e. people for whom first-line therapy was unsuccessful, with an emphasis on their emotional journey. Market research was conducted with 40 people with epilepsy from France, Germany, Italy, Spain, and the UK. Semi-structured interviews were analysed using both a content and framework analysis approach. A content analysis of participants’ expressed emotions was mapped onto the framework to visually illustrate the changes of emotions experienced by people with epilepsy from presentation through to monitoring and follow-up stages, particularly in those treated with more than one anti-seizure medicine. In each stage of the journey, themes and sub themes were identified under the overarching headings “life is turned upside down” (presentation), “period of learning” (diagnosis), “aspirations and experimentation” (treatment), and “out on a limb” (monitoring and follow-up). The research identified key unmet needs and opportunities for people with epilepsy to improve their subjective experiences at different stages of their disease journey. The opportunities recommended are: (1) establishing and promoting support networks from presentation to monitoring and follow-up stages; (2) accelerating pathway to diagnosis; (3) provide opportunities to discuss the diagnosis with people with epilepsy; (4) clarify treatment change guidelines for patients; and (5) developing a shared treatment decision-making tool. Findings have the potential to drive change at an individual level as well as a healthcare level.